MODEL DEVELOPMENT UNDER THE EXERCISE OF TECHNIQUE SERVICES, THE SERVICE AND IN VOLLEYBALL CEKIS (A Study on the Development of Women Athletes Volleyball Level Intermediates in Sigli Town-Aceh) - Irfandi Irfandi; Sugiyanto Sugiyanto; Agus Kristiyanto (JOURNAL OF EDUCATION SCIENCE, 2015)
The background for this study is the ability of a service under the mastery of technique, top service and the ability to serve cekis in a volleyball game where before conducting research there are a number of athletes who have so perfectly mastered, especially in the mastery of the technique, which occurred in mid-level women athletes (Intermediate) the ball club Volly in Sigli town. This study aims to develop a wide range of draft model design engineering practice, and to develop the initial product manufacturing, testing implement small group, large group test, and implement test the effectiveness of the product, so as to obtain results in the form of improved quality of training and technical mastery of athletes, particularly servicing over , lower servicing and cekis in volleyball game at the mid-level women athletes (Intermediate) Bolavolli club in the city of Sigli.Research development or better known as the research and development carried out at the club Bolavolli in Sigli town. The subjects of the study is the son of middle-level athletes, amounting to 22 athletes from the club volleyball PLN Pidie, and 22 athletes from Metro-Sigli volleyball club and volleyball club Corolla (Sigli Volleyball Club). Small group test phase carried out in club volleyball PLN Pidie, followed by a large group test conducted in volleyball club Metro-Sigli. While the implementation phase of product effectiveness test conducted in the Metro-club volleyball and club volleyball Sigli Corolla (Sigli Volleyball Club).This study was able to develop the skills training model figure mainly "service engineering practice models top, bottom and cekis services at the secondary level women athletes Bolavolli club in the city of Sigli. Results mastery of technical skills training model of servicing the top, bottom and cekis servicing obtained based on: 1) Summary data of the percentage of questionnaires and validation by a number of experts were obtained with an average score of 67% and 73%, and it was included in the category quite valid, it means the product service engineering skills training models above, below and cekis service so that it can be used and applied as a model practice guidelines on Bolavolli club mid-level women athletes (Intermediate). Percentage data model results are tested on small groups derived from the mastery of technical skills training model of the athletes which amounted to 81.10%, which means that a valid use, and a large group practice models gained mastery over the technical servicing and servicing under the bolavolli amounted to 85.34 % means that the product is valid to use, so it can be interpreted as if the models developed in real capable of delivering results, and extraordinary contribution accurate, especially in the mastery of technique training models servicing top, bottom and cekis services in bolavolli.Thus, to interpret the results of the development of a model figure for a given treatment group, in which case there is a significant difference between the groups before being given treatment when compared with the group after being given treatment. Based on data from the pretest-posttest athletes showed a mastery of the results of technical skills training models amounted to 62.27%, and thereafter the product models (the process of treatment) then the effect of increased very significantly to the mastery of technical skills training model products with obtaining results amounting to 67.27%. Differences in the form of percentage figures is a result of the result of the provision and application of product models (such as treatment), where the impact of a given product models and demonstrate a very remarkable effect significant at deeper levels, in terms of mastery of product models mainly servicing engineering practice models above , lower servicing and cekis in bolavolli.Keywords: design training models, bolavolli, servicing top, bottom servicing, cekis, treatment, and research and development, or R and D.